Review of current clinical guidelines for the diagnosis and treatment of urinary tract infections in women - О. А. Бурка; Т. М. Тутченко; А. В. Шумицький (Publishing House TRILIST, 2019)
Recurrent urinary tract infections in women is a challenging issue for many specialists including gynecologists. The article provides an overview of current (2018-19) evidence based recommendations on causes, risk factors and algorithms for diagnosing urinary tract infections in women, as well as current views on asymptomatic bacteriuria. New clinical guidelines focus on the need to pay greater attention to the problem of antibiotic resistance, which continues to grow primarily due to the excessive and often unsystematic use of antibacterial drugs. The most common pathogen of acute and recurrent uncomplicated cystitis is Escherichia coli, less common Staphylococcus saprophyticus, Klebsiella pneumoniae, Proteus mirabilis. The most common cause of urethritis in women of reproductive age is sexually transmitted infections: Neisseria gonorrhea, Chlamydia trachomatis, Trichomonas vaginalis, Mycoplasma spр.., Ureaplasma spp. In postmenopausal women non-communicable causes predominate. According to the American Urological Association, the Canadian Urological Association, the Society of Urodynamics, Female Pelvic Medicine & Urogenital Reconstruction recommendations from 2019 all women with clinical manifestations of urethritis/cystitis should undergo gynecological examination and comprehensive laboratory examination. The main signs of urinary tract infection in general urine analysis are pyuria; presence of nitrites; minor or moderate proteinuria; changes in physical properties, presence of erythrocytes (nonspecific signs). Of great importance for the effective treatment of recurrent urinary tract infections is urine culture with definitions of the sensitivity of the pathogens to antibiotics. The effectiveness of urine culture tests depends on the accuracy of biomaterial collection and the conditions for its storage/transportation at the preanalytical stage. Because of the similarity of clinical manifestations of cystitis with urethritis, the cause of which in most cases is sexually transmitted infections, all women need undergo comprehensive clinical and laboratory examination, including gynecological examination and modern diagnosis of sexually transmitted infections.